Environmental factors associated with liana community assemblages in a tropical forest reserve, Ghana. (24th September 2014) - Addo-Fordjour, Patrick; Rahmad, Zakaria B.
Abstract: This study determined variation in liana diversity, composition and community structure in different topographic habitats, as well as the environmental factors associated with them in the Atewa Range Forest Reserve, Ghana. The above-mentioned liana assemblage attributes were examined in thirty 40 × 40-m plots, randomly demarcated within three topographic habitats at different average altitudes (hill bottom: 85.6 m asl, hill slope: 343 m asl, plateau: 641 m asl). Soil properties, altitude and slope angle were determined for the plots. Using multiple stepwise regression, non-metric multidimensional scaling analysis, and analysis of similarity, environmental factors that influenced the above-mentioned attributes of liana assemblages were determined. The findings revealed significant variation in liana diversity, composition and community structure among the topographic habitats. Liana species composition related with soil P, Mg and moisture, and altitude. Soil Mg and P associated positively with species composition in the hill-bottom habitat while altitude and soil moisture related negatively with it. A reverse trend occurred in the other habitats. Five environmental factors related significantly with liana diversity and community structure as follows – species richness: soil Ca and Mg, altitude; Shannon diversity: soil Ca, altitude; abundance: soil moisture and P, altitude; basal area: soil moisture, P.